If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 6x + 2 + 9 = 3x + 5 + 9x Reorder the terms: 2 + 9 + 7x + 6x = 3x + 5 + 9x Combine like terms: 2 + 9 = 11 11 + 7x + 6x = 3x + 5 + 9x Combine like terms: 7x + 6x = 13x 11 + 13x = 3x + 5 + 9x Reorder the terms: 11 + 13x = 5 + 3x + 9x Combine like terms: 3x + 9x = 12x 11 + 13x = 5 + 12x Solving 11 + 13x = 5 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 11 + 13x + -12x = 5 + 12x + -12x Combine like terms: 13x + -12x = 1x 11 + 1x = 5 + 12x + -12x Combine like terms: 12x + -12x = 0 11 + 1x = 5 + 0 11 + 1x = 5 Add '-11' to each side of the equation. 11 + -11 + 1x = 5 + -11 Combine like terms: 11 + -11 = 0 0 + 1x = 5 + -11 1x = 5 + -11 Combine like terms: 5 + -11 = -6 1x = -6 Divide each side by '1'. x = -6 Simplifying x = -6
| 180=(x+96)+5x | | 13-6/5a=6 | | 5(4x+7)=-75 | | 1/2*4*3 | | 8x^2+2x=7x^2-2x+32 | | x+42=2x+1 | | 3+4=19 | | 10x-5=20-6 | | y=4w^2+450/x | | 8x-6=14-20 | | X^2-3x-60=0 | | 7/5+4/5=89/30+7/6x+5/6 | | x=24+4 | | -2(x+3)-2=-4(a-4) | | 3x-5x=6x+12 | | X=24y+4 | | 6(3x+3)=24 | | 1/2m+6=18 | | (8x-4)(9x+7)=0 | | 3/q=5/q+4 | | 1/12x^2-12=0 | | x^2-20+10x=180 | | 2x/6+14=x/4-7 | | 3/x+1=4/x-1 | | 4(x-6)=24 | | r=5d(60-t) | | r=1d(60-t) | | 6x-3(-4x-17)=-75 | | -24+p+8=4+3p | | -7x+6(6x-11)=195 | | 6a^2-a-12=0 | | -15/11=-25/88w |